Evaluación de cultivares de maiz de grano amarillo en doce localidades de Panamá - Alvarado D, A.=700 1 Pérez, D.; De Gracia, N.; González, A.; Quiroz, E.; Ruiz, J.C.; Carranza, L.; Camargo, I.
Sumario (Es)
Ilus.
Keywords: ZEA MAYS; ENSAYOS DE VARIEDADES; PANAMA